Action Understanding Promoted by Interoception in Children: A Developmental Model - Zhou, Hui; Gao, Qiyang; Chen, Wei; Wei, Qiaobo (Frontiers in Psychology, 2022)
Children's action understanding develops from simple associative learning to mentalizing. With the rise of embodied cognition, the role of interoception in action observation and action understanding has received more attention. From a developmental perspective, the present study proposes a novel developmental model that explores how interoception promotes children's action understanding across ages. In early infancy, most actions observed in infants come from interactions with their caregivers. Babies learn about action effects through automatic interoceptive processing and interoceptive feedback. Interoception in early infancy is not fully developed, such as the not fully developed gastrointestinal tract and intestinal nervous system. Therefore, in early infancy, action understanding is based on low-level and original interoceptive information. At this stage, after observing others’ actions, infants can create mental representations or even imitate actions without external visual feedback, which requires interoception to provide internal reference information. By early childhood, children begin to infer other people's action intentions by integrating various types of information to reach the mentalizing level. Interoception processing requires the integration of multiple internal signals, which promotes children's information integration ability. Interoception also provides inner information for reasoning about action intention. The present review also discussed the neural mechanisms of interoception and possible ways by which it could promote children's action understanding. In early infancy, the central autonomic neural network automatically processes and responds to caregivers’ actions on infants, providing interoceptive information for infants’ action understanding. In infancy, the growth of the somatomotor system provides important internal reference information for observing and imitating infants’ actions. In early childhood, the development of children's interoception facilitates the integration of internal and external information, which promotes the mentalization of children's action understanding. According to the proposed developmental model of children's action understanding promoted by interoception, there are multi-level and stage-dependent characteristics that impact the role of interoception in children's action understanding.